Policy Responses in Emerging Economies to International Agricultural Commodity Price Surges - Jones, Darryl (OECD Food, Agriculture and Fisheries Papers, 2010)
This report examines and classifies policy responses in ten major emerging economies to the rise in international agricultural commodity prices in 2006-08. It also analyses impacts of these responses on the domestic market to evaluate their effectiveness in meeting stated policy objectives. The report separates government responses into four major types: market interventions to limit the rise in food prices, market interventions to control inflation, assistance to consumers through safety nets and support to producers. As an indication of the relative importance of these responses in a given country, the report estimates the fiscal costs of policies applied. Developments in trade flows, price transmission, inflation, consumption and production were used to investigate impacts on domestic markets and to draw policy conclusions. Market interventions to minimise the impact on consumers were not always successful, even if trade flows were disrupted, and had taxing effects on farmers who could not benefit from higher international prices. These taxing effects were often partly compensated by increased input-linked support to farmers, which had a relatively high fiscal cost in some instances